EFFECTS OF TRUNK CONTROL EXERCISE WITH SWISS BALL IN IMPROVING TRUNK PERFORMANCE IN STROKE PATIENTS-SINGLE BLINDED STUDY. - JESSE MAGH; G.DEEPTHI; R.ARUNACHALAM (International Journal of Pharma and Bio Sciences, 2016)
Trunk control requires appropriate sensorimotor ability of the trunk in order to provide a stable foundation for balance functions in patients with stroke. Concentrating on trunk strengthening exercises to improve their balance and make them independent. Our study focused on investigating the comparative efficacy of the two interventions i.e. effects of trunks exercise with and without Swiss ball in improving trunk performance in stroke patients. Twenty Subjects were selected based on inclusion and exclusion criteria from OPD of Saveetha physiotherapy Chennai. The subjects were allocated equally into two groups. The trunk performance, balance was assessed before and after the intervention using the Trunk Impairment Scale and The Berg Balance scale respectively. Group-A received conventional physiotherapy and Swiss ball exercises for trunk and Group-B received conventional physiotherapy and plinth exercise for trunk. This study shows statistically significant improvement in trunk control (p=0.0177) and balance (p=0.0019) in group-A treated with a Swiss ball.